The Influence of Brand Experience, Brand Satisfaction, and Perceived Quality on Brand Loyalty Toward Bottled Drinking Water Products (AMDK) - Nabila Putri Sayekti; Anton Agus Setyawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In recent years, branding theory has increasingly focused on understanding the relationship between consumers and brands. A brand serves as a symbolic and functional bridge between buyers and sellers, facilitating trust, communication, and emotional connections (Şahin et al., 2011). It plays a key role in influencing consumer purchasing decisions. A brand represents an offering from the seller to the consumer that consistently conveys its character, utility, and assurance of quality (Suntoro & Silintowe, 2020). In this context, "character" refers to the brand's personality or image, "utility" signifies both the practical benefits of the product and its role in the consumer's life, and "assurance of quality" reflects the reliability and trustworthiness of the brand. Consequently, consumers are more likely to make repeated purchases of a particular brand, as they develop trust and confidence in its consistency. This study aims to explore the underlying factors of brand experience, brand satisfaction, and brand loyalty. Brand loyalty, in this case, encompasses emotional attachment, trust, and habitual behavior towards a brand. A quantitative approach is employed to collect data via an online questionnaire. The research uses purposive sampling, which is appropriate as it targets individuals with relevant insights into their experiences and attitudes towards the brand, ensuring that the sample aligns with the study’s objectives. This non-probability sampling method allows for a more focused exploration of consumer-brand relationships, compared to generalizing from a broader population.